Quality of life in multiple scenarios: The impact of work mode and social contact quantity - Leng, Cheng-Han; Tsai, Chi-Shiun; Chan, Ta-Chien; Lee, Hsuan-Wei (Frontiers in Psychology, 2023)
During the COVID-19 pandemic, many employees were encouraged to temporarily work from home as an attempt to decrease social contact with others. However, the employees' quality of life (QoL) may have been threaten by this mode of working. This study therefore aims to explore the employees' QoL given the new mode of working from home (WFH) as result of the pandemic vs. working in the office (WIO)), the amount of social contact that they were exposed to, and the ratio of face-to-face contact that they had. A total of 803 WFH employees and 588 WIO employees' QoL was assessed during the same time period using the WHOQOL-BREF, which contains four domains: physical health, psychological health, social relationship, and the environment. We then divided the participants into sixteen groups in accordance to the levels of work mode, social contact quantity, and face-to-face contact ratio—forming a case-control study. A differential item functioning (DIF) analysis was used to analyze the responses on the WHOQOL-BREF under the 4-dimensional rating scale model fitting. The results indicated that WFH employees' QoL was superior to that of WIO employees. The relationship between the WFH mode and the employees' QoL was specifically moderated by the amount of social contact and the ratio of face-to-face contact that was experienced. The results further demonstrated that the increased amount of non-face-to-face contact was better for WFH employees' QoL than that of WIO employees. In conclusion, the WFH mode was practical during the COVID-19 pandemic, as our findings indicated that WFH employees' QoL was better than WIO employees' QoL. However, maintaining social connections is equally important as this allows employees to perform better at their jobs and maintain such performance. The employees with a higher number of social support had a better QoL. Additionally, the facets detected as DIF items provided implications for the QoL with regards to the research methodology and insight into factors affecting the employees' QoL.